ANALISIS DAMPAK PEMBELAJARAN DARING BAGI DOSEN DAN MAHASISWA PENDIDIKAN AGAMA ISLAM DI PERGURUAN TINGGI” - Ayu Lika Rahmadani; Mahmud Arif; Fitri Ovianti (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2022)
The purpose of this study is to find out how the impact of online learning during the pandemic, this research method uses qualitative descriptions and uses in-depth analysis by taking sources from interviews, and is based on textbooks, journals and other sources that are in accordance with the research. . And the results of this study indicate that online learning has a major impact on the education system in Indonesia, including in universities. Based on the results of interviews with lecturers and students, it was obtained data that the negative impact of online learning for students is that students experience boredom, not being able to reach the internet, while the negative impact of online learning for lecturers is feeling the confusion of lecturers' assessments and it is also difficult to monitor students, then, the positive impact of online learning for students, namely learning independently and responsibly and more, respecting time, getting to know technology and being able to look back at the subject matter taught by lecturers and being cost-effective. Then, the positive impact for lecturers is that lecturers are more technology literate and more creative in making learning media